Effectiveness of Simulation-Based Bridge Resource Management Training for Future Deck Officers - Rizal Rochmansyah, Dony Ferdinal Frengki Simarmata (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) STIP Jakarta, 2025)
This study assesses the effectiveness of high-fidelity simulator-based training in developing Bridge Resource Management (BRM) competencies among nautical cadets preparing to become deck officers. Using a quasi-experimental design, two comparable groups of cadets follow the same navigation curriculum; however, the experimental group receives additional structured simulator scenarios focused on communication, teamwork, workload management, and emergency response in congested and restricted waters. Objective performance data are collected through instructor evaluation rubrics, scenario log files, and automatic tracking of key actions on the bridge. These are complemented by self-assessment questionnaires that measure confidence, perceived teamwork quality, and situational awareness. Statistical analysis compares the progression of both groups and identifies which BRM elements benefit most from simulation. Input from shipmasters and training managers in the shipping industry is used to validate the realism and relevance of the scenarios. The study provides evidence-based recommendations on scenario design, instructor briefing and debriefing practices, and minimum simulator hours needed to produce meaningful improvements in BRM skills aligned with STCW requirements and industry expectations.